CHubungan Tingkat Beban Pekerjaan terhadap Kejadian Kifosis pada Buruh Panggul di Pasar Tradisional Tanjung Jember Periode Bulan Januari 2020 - Totalenesya Reforrent Sutikno; Dion Krismashogi Dharmawan; Erfan Efendi (Journal of Islamic Medicine, 2022)
Background: Kyphosis is  vertebrae disorder characterized with increased of vertebrae curve in sagital line of 40o Cobb angle. Kyphosis is caused by degenerative proces,, neuromuscular disease, tumor, trauma, congenital abnormalities and unergonomic posture at the moment of carriying weights. One of kyphosis risk factor is excessive weights on the back in long duration. The complication of kyphosis such as vertebrae compression fracture could cause pain and deformities. Objective: Purpose of this research is to describe the correlation between workload level in carrier workers towards kyphosis at Tanjung Market, Jember. Methods: This research was observational analitic, cross sectional method, and total sampling. The respondents were 32 male carrier workers and 32 controls.. Data was obtained by interview and Cobb angle measurement on 1st and 12th thoracal vertebrae using inclinometer. Statistical test was done by Spearman correlation test. Results: The data analysis showed that p value for working time, work tenure, and transport weights toward kyphosis prevalence sequentially were 0,778; 0,326; and 0,739. Male carrier workers in Tanjung Traditional Market used to carry 50-100 Kg of weights once they start to transport. The working time of the carrier workers each day were seven hours and 15 years for work tenure in average. There were two carrier workers (6,2%) suffering of kyphosis (50 years old) with working time 8 hours per day, 10 years for work tenure, and 50 Kg for transport weights.. Conclusion: This research had proven that there is no any correlation between working time, work tenure, and carried load level towards kyphosis in carrier workers of Tanjung Market Jember.